2019
DOI: 10.1002/celc.201901045
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Interpenetrating Network‐Structured Single‐Ion Conduction Polymer Electrolyte for Lithium‐Ion Batteries

Abstract: A novel quasi solid single‐ion polymer electrolyte with semi‐interpenetrating network (semi‐IPN) structure has been prepared. The lithium‐ion conduction membrane is composed of both the cross‐linked lithiated poly‐2‐acrylamido‐2‐methylpropane sulfonic acid (PAMPS‐Li) as a polyanionic single‐ion lithium salt source and the high molecular weight polyethylene oxide (PEO) as a polymer matrix, in which the two components show great compatibility due to the special semi‐IPN structure. For such quasi‐solid electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
(84 reference statements)
0
21
0
Order By: Relevance
“…To illustrate this point, Zhao and co‐workers produced semi‐IPN structured membranes based on crosslinked lithiated poly‐2‐acrylamido‐2‐methylpropanesulfonic acid (PAMPS‐Li) and PEO with the excellent tensile strength of 12 MPa and elongation at break of 250%. [ 255,256 ] Yang and co‐workers also prepared a 3D network polymer electrolyte by crosslinking diglycidyl ether of bisphenol‐A (DEBA), poly(ethylene glycol) diglycidyl ether (PEGDE), and diamino‐poly(propylene oxide) (DPPO) that showed improved toughness and flexibility with effective suppression of Li dendrite growth without significant loss of σ. The tensile strength of the material reached 7.6 MPa with a maximum strain of 121.6%.…”
Section: Spes For Li‐based Secondary Batteriesmentioning
confidence: 99%
“…To illustrate this point, Zhao and co‐workers produced semi‐IPN structured membranes based on crosslinked lithiated poly‐2‐acrylamido‐2‐methylpropanesulfonic acid (PAMPS‐Li) and PEO with the excellent tensile strength of 12 MPa and elongation at break of 250%. [ 255,256 ] Yang and co‐workers also prepared a 3D network polymer electrolyte by crosslinking diglycidyl ether of bisphenol‐A (DEBA), poly(ethylene glycol) diglycidyl ether (PEGDE), and diamino‐poly(propylene oxide) (DPPO) that showed improved toughness and flexibility with effective suppression of Li dendrite growth without significant loss of σ. The tensile strength of the material reached 7.6 MPa with a maximum strain of 121.6%.…”
Section: Spes For Li‐based Secondary Batteriesmentioning
confidence: 99%
“…[ 153 ] Thus, an assembly of cross‐linked lithiated poly‐2‐acrylamido‐2‐methylpropane sulfonic acid and high molecular weight PEO formed a quasi‐solid single‐ion semi‐IPN electrolyte, which exhibited good mechanical stability, minimal crystallinity, a high tLi+ (0.77), high discharge capacity, and an acceptable ionic conductivity of 1.34 × 10 −5 S cm −1 at 60 °C attributed to the excellent compatibility of the two composites. [ 154 ] Enhanced ionic conductivity was also obtained for semi‐IPN electrolytes consisting of plasticizers and an oligo(ethyleneoxy)cyclotriphosphazene based cross‐linker, while it was found that such electrolytes have flame retardant ability (Figure 7b). [ 155 ]…”
Section: Well‐defined Polymer Matricesmentioning
confidence: 98%
“…After plasticized by electrolyte of PC/EC (1:1, V:V), the ionic conductivity of the SIPE was 1.34 × 10 −5 S cm −1 at 333 K, with LTN of 0.77 and ESW of 4 V. Implementation in a Li||LFP cell delivered a capacity of 140 mAh g −1 at 333 K and showed a capacity retention of 90.4% after 100 cycles. [127] A new type of fast Li-ion conducting electrolyte based on imidazolate COFs was reported recently. The imidazolate component in the backbone offers highly electronegative sites, immobilizing the anion, and solvating the Li + ions easily.…”
Section: Single-ion Gel or Quasi Solid-state Polymer Electrolytes (Simentioning
confidence: 99%
“…[40,61,62,[66][67][68]70,71,75,[82][83][84][85]88] SPEs: orange dots [89][90][91][92][93][94][95][96]99] ). b) Single-ion polymer electrolytes (GPEs: blue dots, [109,111,[116][117][118][119][120][121][122][123][124][125][126][127][128] SPEs: orange dots [108,114,[129][130][131] ). All-solid-state and single-ion polymer electrolytes will still be important development directions for polymer electrolytes.…”
Section: Summary Of Polymer Electrolytesmentioning
confidence: 99%